Comparison of CMM and Micro-CT Volumetric Analysis of Polyethylene Tibial Knee Inserts in Total Knee Replacement - Wei Jiang; Cuicui Ji; Huaxing Xiao; Zhongmin Jin; Yuntian Dai (International Journal of Polymer Science)
Ultrahigh molecular weight polyethylene (UHMWPE) bearings are used widely in orthopaedic joint replacement as a prominent material for improving the longevity, which is dramatically influenced by wear of polyethylene. Polyethylene tibial knee components from knee simulators under two different input conditions were analyzed using CMM and Micro-CT measurement techniques for volumetric loss with gravimetric measurement as reference. Based on the coordinates and image slices obtained, the surface curve fitting and image digitization methodology were used for the creation of nominal “original” surface in the case of no prewear data provided. The comparison results indicate that gravimetric remains the gold standard and the CMM measurement took less time and had better precision, accuracy, and repeatability compared to Micro-CT measurement technique.